Risk assessment of SunCon: An empirical study of construction sector in Malaysia - Kah, Yan Siah; Irene, Wei Kiong Ting (Penerbit Universiti Malaysia Pahang, 2023)
Risk assessment plays a crucial and vital role in the construction sector. This research paper presents an empirical study on the risks associated with SunCon, an extraordinary pure-play construction company in Malaysia. The objectives of this study are to analyse the potential risks exposed to SunCon company and suggest risk management strategies that could help to mitigate or control those potential risks. The research conducted primarily focuses on the financial risk exposure of SunCon by analysing the secondary data that gathered from annual report. The research conducted a time-series comparative analysis of SunCon's financial performance from 2018 2022. The quantitative approach is used in this research methodology in order to evaluate the risk exposure direct to SunCon in terms of the company's financial performance. The risk measurement analyses the risk exposed including Z-score, liquidity risk, debt risk, credit risk, and interest rate risk. The findings provide an empirical analysis of SunCon's risk management strategies in terms of their financial risk over the past five years. To accomplish the objectives of the study, the study also suggested the risk control strategies that can be implemented by SunCon to mitigate the risks. In conclusion, this research provides significant implications on potential risks exposed to SunCon and the strategies to mitigate those risks. This research paper put concerns of the importance of risk management practices in the dynamic construction sector.